COMPETITIVENESS OF LEADING COMMODITIES TO SUPPORT DEVELOPING REGION OF AGROTOURISM - Murwatiningsih Murwatiningsih; Dyah Maya Nihayah; Shanty Oktavilia (Universitas Islam Indonesia, 2013)
AbstractThe aim of the research is to seek the competitiveness of the leading commodity in Semarang city which supports the development of centre commodity in agrotourism area. The method of analysis is leading sector, scoring analysis and capacity asessment through FGD. The result of the research reveals that leading commodities are Durian, Longan, Water Apple, and Rambutan. It is found that subdistrict Gunungpati and Mangunsari are ready to be the centre of horticulture commodity because its strategic location. It is located nearby Jatibarang reservoir (potential to be a tourism village), its cultivation is relatively successful, accessable transportation, and good management. Hence, it can be the pilot project area.Key words: competitiveness, centre, commodity, horticultureJEL Classification: O20, Q10AbstrakKesejahteraan petani tidak meningkat karena daya saingnya rendah dan pengelolannya tidak optimal. Tujuan penelitian, untuk melihat daya saing komoditas unggulan Kota Semarang untuk mendukung pengembangan sentra komoditas di kawasan agrowisata. Metode analisis yaitu sektor basis, analisis scoring serta capacity assessment melalui FGD. Hasil penelitian menunjukkan komoditas yang diunggulkan di Gunungpati adalah durian, klengkeng, jambu air dan rambutan. Kelurahan Gunungpati dan Mangunsari siap dijadikan sentra komoditas hortikultura di Kecamatan Gunungpati karena letaknya strategis- dekat dengan waduk Jatibarang (dapat menjadi desa wisata), budidaya relatif lebih berhasil, transportasi dan akseptibilitas lebih mudah, pengelolaannya bagus sehingga sudah menjadi daerah percontohan.Kata Kunci: daya saing, sentra, komoditas, hortikulturJEL Classification: O20, Q10